P-051. Diagnosis ways of chronic HBV cases - Tosun, Selma (Turk J Gastroenterol, 2019)
INTRODUCTION: The aim of this study was to determine how HBsAg positivity was diagnosed. METHODS: Health Science University Izmir Bozyaka Education and Research Hospital Viral Hepatitis polyclinic patients were followed-up in the records of the patients were examined. FINDINGS: A total of 3981 chronic HBV cases were evaluated among 2060 (51%) male and 1921 female patients aged between 18–82 years. It was determined that the highest rate of diagnosis was 31.5% (1253/3981) blood testing for any reason. Following this, blood donations and examinations performed during pre-marital examination; the presence of another chronic hepatitis case in the family and the examinations performed during pregnancy screening. The diagnosis of 10% of the cases was made before the operation for any reason. CONCLUSION: The diagnosis of one third of HBsAg positive cases in the study group was made during the examinations performed for any reason. For this reason, all physicians should be aware of this issue and refer to the relevant experts. Blood donation is also important in detecting cases. In our country, since 2003, a blood examination is done for some infectious diseases before marriage. This practice seems to be useful for identifying new cases and providing necessary information and vaccination to their partners. Although the application of HBsAg in pregnancy is not common in our country, the diagnosis of some cases has been made in this way. The rate of diagnosis is not high due to the presence of another case of chronic HBV in the family. This result may be related to the fact that most chronic HBV cases are unaware of their condition or ignore. Again, since 9% of the cases were diagnosed in pre-operative screening tests, it is suggested that these scans should be continued and that surgical branch physicians should be informed about the issue. As a result, HBsAg positivity can be diagnosed in many ways, but the cases are mostly asymptomatic and can be missed. Therefore, it will be useful to continue screening methods and to increase awareness of health workers on this issue.